Decisions around Deceased Organ Donation in Young South Asian Individuals in the United Kingdom - Pinky Kotecha; Rahul Shah; Siddarth Raj; Amar Rai; Abdullah Khawaja; Sunil Daga (Saudi Journal of Kidney Diseases and Transplantation, 2022)
There is a large disparity between the demand and availability of organs for transplantation from within the UK's ethnic minority groups. Our aims were to identify the perceptions, knowledge of and level of engagement with organ donation since the law changed in England in 2020. A questionnaire survey using Google Forms was designed based on prior literature and information on NHSBT website. It was distributed through media outlets and cultural/professional organizations. Status on Organ Donation Registry and Quiz scores were analyzed against multiple variables. Three hundred and sixty-five people between 18 and 24 years old completed the questionnaire. 72.3% were female, 57% were health-care students, 86.3% were of South Asian ethnicity, and 11% were immigrant respondents. Overall, 43.6% were registered to donate. South Asian groups, particularly those of Pakistani ethnicity and migrant students, were less likely to register to donate. Being more knowledgeable about the organ donation process, females, nonreligious groups, and health-care students are more likely to be registered to donate. This study identified barriers around deceased organ donation decisions and demonstrates the need for further targeted and continual education to the young South Asians individuals, to produce positive associations that will percolate to older and future generations.